2014
DOI: 10.1089/vbz.2014.1605
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Phylogenetic Reconstructions of Rift Valley Fever Virus: The 2010 Northern Mauritania Outbreak in the Camelus dromedarius Species

Abstract: Rift valley fever (RVF) is a mosquito-borne disease of domestic and wild ruminants caused by RVF virus (RVFV), a phlebovirus (Bunyaviridae). RVF is widespread in Sub-Saharan Africa. In September of 2010, an RVF outbreak occurred in northern Mauritania involving mass abortions in small ruminants and camels (Camelus dromedarius) and at least 63 human clinical cases, including 13 deaths. In camels, serological prevalence was 27.5-38.5% (95% confidence interval, n=279). For the first time, clinical signs other tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Because of this, the risk of triggering RVF epidemics is increased by the combined effect of the peak in livestock mobility, the rapidity of their movements and the higher vector abundances. This might well have happened in 2010, when an RVF outbreak occurred in northern Mauritania after exceptional rainfall: Mauritanian farmers brought their animals (small ruminants, cattle, dromedaries)—and most likely the RVF virus as well, from southern Mauritania by truck to benefit from the unexpected resources in surface water and grasslands [ 52 , 53 ]. Antibodies against RVF virus were later found in Moroccan dromedaries [ 54 ], suggesting that the spread of this virus in Morocco had occurred via livestock trade, as it had been the case between the Horn of Africa and the Arabic peninsula in 2000 [ 55 ], or between the East African mainland and the Comoros Archipelago—and Madagascar in 2006-2008 [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because of this, the risk of triggering RVF epidemics is increased by the combined effect of the peak in livestock mobility, the rapidity of their movements and the higher vector abundances. This might well have happened in 2010, when an RVF outbreak occurred in northern Mauritania after exceptional rainfall: Mauritanian farmers brought their animals (small ruminants, cattle, dromedaries)—and most likely the RVF virus as well, from southern Mauritania by truck to benefit from the unexpected resources in surface water and grasslands [ 52 , 53 ]. Antibodies against RVF virus were later found in Moroccan dromedaries [ 54 ], suggesting that the spread of this virus in Morocco had occurred via livestock trade, as it had been the case between the Horn of Africa and the Arabic peninsula in 2000 [ 55 ], or between the East African mainland and the Comoros Archipelago—and Madagascar in 2006-2008 [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…An important question underlying these analyses is the role that animal mobility might play in the spread of animal and zoonotic diseases in the region. For example, animal movements may contribute to the spread of Rift Valley fever (RVF) in the Sahelian region of Mauritania, and from Mauritania to Senegal [ 37 , 38 ]. The network structure predicted by this model may provide input for an epidemiological model of RVF or other important diseases affecting the region, such as Peste des petits ruminants (PPR) [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Absence of clinically recognized symptoms of RVF infections with noticeable outbreaks of abortion may lead to underestimation of the importance of the disease in Sudanese camels. In contrast, clinical signs other than abortions were reported among camels in RVF outbreak in Mauritania, including hemorrhagic septicemia and severe respiratory distress [ 26 ]. This observation indicated that the pathogenicity of RVFV in the dromedary camels has not been investigated sufficiently.…”
Section: Discussionmentioning
confidence: 99%
“…In epidemiological surveys, high prevalence rates of 45 % and 38.5 % for RVFV seropositivity were reported among camels in Tanzania and Mauritania, respectively [ 26 , 27 ]. In Niger, high prevalence rate of RVFV seropositivity of 47.5 % was also reported in camels in some region of the country [ 34 ].…”
Section: Discussionmentioning
confidence: 99%